Raman Spectroscopy as a Robust New Tool for Rapid and Accurate Evaluation of Drought Tolerance Levels in Both Genetically Diverse and Near-Isogenic Maize Lines - Altangerel, Narangerel; Huang, Pei-Cheng; Kolomiets, Michael V.; Scully, Marlan O.; Hemmer, Philip R. (Frontiers in Plant Science, 2021)
Improving drought tolerance of crops has become crucial due to the current scenario of rapid climate change. In particular, development of new maize germplasm with increased drought tolerance is viewed as a major breeding goal to ensure sustainable food and feed production. Therefore, accurate rapid phenotyping techniques for selection of superior maize genotypes are required. The objectives of this study were to determine whether the Raman microscopy technique can be applied for accurate assessment of drought-tolerance levels in both genetically diverse and near-isogenic maize lines that differ in their levels of drought-tolerance. We observed real-time changes in the rate of carotenoid degradation in chloroplast due to the strength of the osmotic stress using Raman mapping. Carotenoid degradation is known to be a direct stress response initiated by reactive oxygen species during osmotic stress such as drought. In addition, we showed that the rate of carotenoid degradation correlates directly with the drought tolerance levels in maize genotypes. We conclude that the Raman technique is a robust, biochemically selective and non-invasive phenotyping technique that accurately distinguishes drought tolerance levels in both genetically diverse and near-isogenic maize genotypes. This technique is suitable for field-based early assessment of breeding materials with superior drought-tolerance traits.